Faktor Faktor Yang Mempengaruhi Mahasiswa Dalam Pemilihan Karir Menjadi Auditor Pada Instansi Pemerintah Dan Swasta - Sutan Pandilon; Charoline Cheisvyanny (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to analyze the factors which influence accounting students in choosing accounting career as auditor at both private and government instutions. The factors are financial reward, work environment, labor market consideration, social values, professional recognition, family environment, and personality. The population in this study is accounting students in state and private university of Indonesia. The sample is determined based on the non-probability sampling method. The data used in this study are primary data. This study used a questionnaire 177 respondents. The method of analysis is multiple linear regression analysis. The results showed that work environment, social values, professional recognition, and family environment have no significant effect on career selection as auditor. While the financial reward, labor market consideration, and personality have a positive significant effect on career selection as an auditor.